A Field Study of Internal Auditing. - Churchill, Neil C.; Cooper, William W. (The Accounting Review, 1965)
The article presents results of a field inquiry directed to ascertaining some of the perceptions of internal auditing held by persons who have been subjected to one or more phases of an audit process. It is part of an extensive research effort into the control functions of management, as distinguished from planning and decision making, and more particularly, into auditing as a major instrument of organizational control. The laboratory experiments on audit effects indicate that an audit can exert its influence through an audit report whose preparation is a focus toward which audits are customarily pointed, and through an auditor's actions as seen or heard about by those audited, for example, what the auditor looks at, what he ignores, what be pursues vigorously, how he behaves, etc. The interviews with 52 of the 54 individuals included in this study produced reports that allowed the content coder to classify the extent of each respondent's contact with internal auditors. Almost 75% of the respondents indicated either a neutral or a positive attitude toward the internal auditor and the internal audit.